Pregunta
upstudy study bank question image url

Write the quadratic function in the form \( y=a(x-h)^{2}+k \) and sketch its graph. \( y=x^{2}-4 x \)

Ask by Long Rojas. in the United States
Feb 25,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The quadratic function \( y = x^{2} - 4x \) can be rewritten in vertex form as \( y = (x - 2)^{2} - 4 \). The graph is a parabola opening upwards with its vertex at (2, -4). It has x-intercepts at (0, 0) and (4, 0), and a y-intercept at (0, 0).

Solución

To convert y = x² - 4x into vertex form (y = a(x - h)² + k), follow these steps: 1. Start with the function:   y = x² - 4x 2. Factor out the coefficient of x² (in this case, it’s 1, so nothing changes):   y = x² - 4x 3. Complete the square:   • Take half the coefficient of x: ½(-4) = -2.   • Square it: (-2)² = 4.   • Add and subtract 4 inside the expression:     y = (x² - 4x + 4) - 4 4. Now write the quadratic as a perfect square:   y = (x - 2)² - 4 Thus, the vertex form is:   y = (x - 2)² - 4 Graph Details:  • Vertex: The vertex (h, k) is (2, -4).  • Axis of Symmetry: x = 2.  • x-intercepts: Set y = 0 in the original equation:   x² - 4x = 0 ⟹ x(x - 4) = 0 ⟹ x = 0 or x = 4.  • y-intercept: Set x = 0:   y = 0² - 4(0) = 0, so the point is (0, 0). Sketch Instructions:  1. Plot the vertex at (2, -4).  2. Draw the axis of symmetry, a vertical line through x = 2.  3. Mark the x-intercepts at (0, 0) and (4, 0) and the y-intercept at (0, 0).  4. Draw a smooth U-shaped (upward opening) curve passing through these points. This graph represents the parabola y = (x - 2)² - 4.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

To rewrite the quadratic function \( y = x^2 - 4x \) in the form \( y = a(x-h)^2 + k \), we need to complete the square. 1. Start with \( y = x^2 - 4x \). 2. Take half of the coefficient of \( x \) (which is -4), square it, and add and subtract that value inside the function. Half of -4 is -2, and squaring it gives 4. 3. Rewrite the expression: \[ y = (x^2 - 4x + 4) - 4 = (x - 2)^2 - 4. \] So, in vertex form, this function is \( y = (x - 2)^2 - 4 \), where the vertex is \( (h, k) = (2, -4) \). Now sketching the graph: 1. The vertex is located at \( (2, -4) \). 2. The parabola opens upwards (since the coefficient of \( (x - 2)^2 \) is positive). 3. The axis of symmetry is the line \( x = 2 \). 4. For additional points, we can test \( x = 1 \) (which gives \( y = -3 \)), \( x = 3 \) (which also gives \( y = -3 \)), and \( x = 0 \) (which gives \( y = 4 \)). The graph looks like a 'U' shape opening upward with its vertex at \( (2, -4) \).

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad